Fire evolution in the radioactive forests of Ukraine and Belarus: future risks for the population and the environment. Issue 1 (1st February 2015) - Evangeliou, N.; Balkanski, Y.; Cozic, A.; Hao, W. M.; Mouillot, F.; Thonicke, K.; Paugam, R.; Zibtsev, S.; Mousseau, T. A.; Wang, R.; Poulter, B.; Petkov, A.; et al.
Abstract : In this paper, we analyze the current and future status of forests in Ukraine and Belarus that were contaminated after the nuclear disaster in 1986. Using several models, together with remote‐sensing data and observations, we studied how climate change in these forests may affect fire regimes. We investigated the possibility of 137 Cs displacement over Europe by studying previous fire events, and examined three fire scenarios that depended on different emission altitudes of 137 Cs, assuming that 10% of the forests were affected by fires. Field measurements and modeling simulations confirmed that numerous radioactive contaminants are still present at these sites in extremely large quantities. Forests in Eastern Europe are characterized by large, highly fire‐prone patches that are conducive to the development of extreme crown fires. Since 1986, there has been a positive correlation between extreme fire events and drought in the two contaminated regions. Litter carbon storage in the area has doubled since 1986 due to increased tree mortality and decreased decomposition rates; dead trees and accumulating litter in turn can provide fuel for wildfires that pose a high risk of redistributing radioactivity in future years. Intense fires in 2002, 2008, and 2010 resulted in the displacement of 137 Cs to the south; the cumulative amount of 137 Cs re‐deposited over Europe was equivalent to 8% of that deposited following the initial Chernobyl disaster. However, a large amount of 137 Cs still remains in these forests, which could be remobilized along with a large number of other dangerous, long‐lived, refractory radionuclides. We predict that an expanding flammable area associated with climate change will lead to a high risk of radioactive contamination with characteristic fire peaks in the future. Current fire‐fighting infrastructure in the region is inadequate due to understaffing and lack of funding. Our data yield the first cogent predictions for future fire incidents and provide scientific insights that could inform and spur evidence‐based policy decisions concerning highly contaminated regions around the world, such as those of Chernobyl.